Mimicking Mills’ syndrome: progressive spastic hemiparesis on upper motor neuron dominant amyotrophic lateral sclerosis - Montemayor, Elizer M.; Marissa T. Ong; Renato D. Dejan J.; Evelyn O. Chua-Ley (International Journal of Research in Medical Sciences, 2023)
Mills’ syndrome is an idiopathic, slowly progressive, spastic hemiparetic variant of primary lateral sclerosis (PLS). Despite this classic definition, this syndrome has recently been suggested to be present on all the variants of motor neuron disease (MND) spectrum (ALS, PLS or UMNdALS). Authors presented a 63 years old male with history of gradually progressive right-side hemiparesis associated with dysarthria and dysphagia. Neurologic examination revealed intact cognition, weak bilateral orofacial muscles, marked right-side spasticity with hyperreflexia and mild sensory deficit, progressing to right-upper extremity atrophy upon follow-up. Relevant blood and CSF examinations were within normal limits. MRI of brain and cervical spine were unremarkable. electromyography (EMG), nerve conduction velocity (NCV), facial motor and blinks studies initially revealed no evidence of lower motor neuron involvement. Based on the revised El escorial criteria, patient was diagnosed as upper motor neuron dominant amyotrophic lateral sclerosis (UMNdALS) mimicking the classic PLS-Mills’ hemiparetic variant.